Analisis Disiplin Kerja Pegawai Negeri Sipil di Badan Pendidikan dan Pelatihan Provinsi Jawa Tengah - Aprilina Kartika Sari; Ida Hayu Dwimawanti; Herbasuki Nurcahyanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
This research aims to analyze the discipline of work and factors driving the discipline as well as a barrier to working civil servants Education and Training Department in Central Java Province.Based on the results of the study showed that the discipline of civil servants who are working in Education and Training Department of Central Java Province have not been good. It is seen from the employees who did not arrive timely and not obedient to regulations in the works. Discipline employees work is inseparable from the supporting and restricting factors. Supporting factors from the discipline of work motivation and leadership. While the factor that inhibit employees work discipline is motivation for awarding the prize to an employee who is not clear. Restricting factor of leadership is the absence of punishment for assertiveness employees who violate discipline.Based on the existing obstacles in the achievement of a work discipline employees in Education and Training Department of Central Java Province, the author provides recommendations in the form of: (1) Did the assessment and awarding of the prize to an employee based on clear indicators. (2) Increase in an employee discipline can be exercised with firmness of punishment. Firmness of punishment carried out must be applied to employees who violate discipline work.